1988
DOI: 10.1021/jm00398a026
|View full text |Cite
|
Sign up to set email alerts
|

Arteether, a new antimalarial drug: synthesis and antimalarial properties

Abstract: Arteether (6) has been prepared from dihydroquinghaosu (3) by etherification with ethanol in the presence of Lewis acid and separated from its chromatographically slower moving alpha-dihydroqinghaosu ethyl ether (7). The absolute stereochemistry at C-12 has been determined by 1H NMR data (J11,12, NOESY). Ethyl ethers 6 and 7 showed potent in vitro inhibition of Plasmodium falciparum, and both compounds were highly potent antimalarials in mice infected with a drug-sensitive strain of Plasmodium berghei. Crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
185
0
12

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(204 citation statements)
references
References 4 publications
7
185
0
12
Order By: Relevance
“…The IC 50 values for artesunate and dihydroartemisinin were 1.66 nM and 1.79 nM in the W2/Indochina clone and 2.18 nM and 1.83 nM in the D6/Sierra Leone clone, respectively. 19 In the study of Wongsrichanalai and others, the geometric mean IC 50 values of artesunate (3.22 nM) and dihydroartemisinin (3.24 nM) were also similar in 10 culture-adapted Vietnamese strains. 40 Artesunate is relatively unstable in aqueous solutions, 18 which may imply that the hydrolysis of artesunate to dihydroartemisinin during the 48-hr incubation at 37ЊC may explain why the mean IC 50 values of these two derivatives are within a similar range.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The IC 50 values for artesunate and dihydroartemisinin were 1.66 nM and 1.79 nM in the W2/Indochina clone and 2.18 nM and 1.83 nM in the D6/Sierra Leone clone, respectively. 19 In the study of Wongsrichanalai and others, the geometric mean IC 50 values of artesunate (3.22 nM) and dihydroartemisinin (3.24 nM) were also similar in 10 culture-adapted Vietnamese strains. 40 Artesunate is relatively unstable in aqueous solutions, 18 which may imply that the hydrolysis of artesunate to dihydroartemisinin during the 48-hr incubation at 37ЊC may explain why the mean IC 50 values of these two derivatives are within a similar range.…”
Section: Discussionmentioning
confidence: 85%
“…19,35,37,38 Artesunate is even more active in vitro than artemether and arteether; its activity is about four times greater than that of artemisinin. 19,38,39 Artesunate was almost as active as dihydroartemisinin in our studies. The IC 50 values for artesunate and dihydroartemisinin were 1.66 nM and 1.79 nM in the W2/Indochina clone and 2.18 nM and 1.83 nM in the D6/Sierra Leone clone, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bioassay offers an additional advantage of simultaneously assessing the susceptibilities of different stages of gametocytes to a drug. QHS and NIHO2 were found to be equally toxic to the asexual stages of the chloroquine-resistant FCD-3 isolate employed in this study whereas in other strains dihydroartemisinin has been reported to be a more potent schizontocidal drug (7). Both these compounds exhibited high in vitro gametocytocidal activity at a concentration of 25 ng/ml.…”
mentioning
confidence: 63%
“…dure (Brossi et al, 1988). The chloride acid RCOCl was prepared from the corresponding carboxylic acids by heating with thionyl chloride at 55°C for 3 h and reacting with DHA in the presence of triethylamine in dry dichloromethane at 0°C for 2 h to furnish ester derivatives in 49-58% yields.…”
Section: Artemisinin and Artesunatementioning
confidence: 99%